Towards ultra-stable and dendrite-suppressed Li-metal batteries: Ion-regulating graphene-modified separators - Choi, Wootaek; Park, Minsu; Woo, Sujeong; Kim, Hyunwoo; Kang, Min Sung; Choi, Junghyun; Cho, Sung Beom; Kim, Taehoon; Kim, Patrick Joohyun (Carbon, 2024)
The practical application of metallic lithium (Li) anodes is hindered by nonuniform Li deposition/dissolution, as well as poor electrochemical reversibility during cycling. To address these challenges, surface modification of polymer separators with functional materials has been extensively explored. In this study, two distinct surface-modifying layers composed of MnOx and polydopamine (PDA) are applied to modify the surface of graphene-coated polypropylene separators (G@PP). Both MnOx and PDA, which are formed through the graphene layer, significantly enhance the intrinsic electrolyte wettability of G@PP, resulting in a homogeneous Li-ion flux. Furthermore, the lithiophilic properties revealed by DFT and COMSOL analyses synergize with the hydrophilic characteristics, resulting in a more stable electrochemical performance in Li-metal batteries (LMBs). The enhanced electrolyte permeability of the coating layer allows Li–Cu cells with MnOx-modified graphene-coated PP (MG@PP) and PDA-modified graphene-coated PP (PG@PP) separators to exhibit significantly improved cycle stability compared with Li–Cu cells with G@PP separators. Interestingly, Li–S cells equipped with MG@PP and PG@PP separators exhibit also enhanced electrochemical performance compared with Li–S cells with G@PP separators. These results highlight that surface engineering of separator-coating materials along with hydrophilic and lithiophilic materials enhances both long-term cycle stability and electrochemical kinetics in LMBs.
Keywords: Graphenes; Homogeneous lithium-ion flux; Hydrophilic separator; Hydrophilics; Ion fluxes; Lithium ions; Lithium metal anode; Lithium metals; Polydopamine; Wettability enhanced graphene; Homogeneous Li-ion flux; Hydrophilic separator; Lithium metal anode; Wettability enhanced graphene